Effect of 11 Weeks of Physical Exercise on Physical Fitness and Executive Functions in Children - Mingyang Zhang; Hanna Garnier; Guoping Qian; Shunchang Li (Children, 2023)
Object: The aim of our study was to evaluate and compare the effects of physical exercise interventions on physical fitness and executive functions in children. Methods: Six-year-old children participated in the study and were randomly divided into physical exercise group (PE group, n = 43) and control group (C group, n = 46). The children in the PE group participated in a physical exercise program for 45 min daily, four days a week for 11 weeks. The children in the C group continued with their usual routines. Then, all the children were tested before and after the experiment for body composition (height, weight, BMI), physical fitness (20-m shuttle run test, standing long jump test, grip strength test, 4 × 10 m shuttle run test and sit and reach tests), and executive functions test (animal go/no-go task, working memory span task, simple reaction test and flexible item selection task) before and after the 11-week period. Results: The 11 weeks of physical exercise did not significantly affect the body composition of the children (p > 0.05). The physical fitness and executive functions test results showed that 11 weeks of physical exercise interventions improves physical fitness (cardiopulmonary fitness, muscle strength, speed sensitivity and flexibility quality) and executive functions parameters (inhibitory control, working memory, the reaction time, and cognitive flexibility) in children (p < 0.05, p < 0.01). Conclusion: 11 weeks of physical exercise can improve the physical fitness and executive functions of six-year-old children.